Tiqui Taca Tahfidz: Syarat Quantum Tahfidz Al-Qur’an (QTA) Perspektif Abdurrohman Al-Asy’ari - Khoirul Muhtadin; Oktaviani Permatasari (Institut Agama Islam Sumatera Barat, 2024)
Quantum Tahfidz Al-Qur'an (QTA) or accelerated memorization of the Al-Qur'an is a method developed from quantum learning. This method is inspired by quantum theory in physics. With this method, it is hoped that students can learn and memorize quickly. This research focuses on Abdurrohman's thoughts on the issue of quantum tahfidz or accelerated memorization, with descriptive qualitative analysis using the living Qur'an approach to get a clear picture narratively. The method developed by Abdurrohman Al-Asy'ari focuses on the function of the right and left brain and the role of the teacher in the process of learning and memorizing quickly. Apart from that, Abdurrohman also applies the function of the Al-Qur'an as an intermediary or wasilah in making it easier to memorize the Al-Qur'an. Includes verses that are read as prayers or wirid. Even in its development, the initial words of each verse were used as formulas or keywords for memorizing. With these techniques, which were later called the tiqui taca strategy, Abdurrohman was able to develop learning and memorizing techniques quickly, precisely and in a fun way.